Morphological and hand grip strength characteristics and differences between participants of the 2022 world rowing championship - Busta, Jan; Hellebrand, Jaroslav; Kinkorová, Ivana; Macas, Tomáš (Frontiers in Sports and Active Living, 2023)
Rowing is a strength endurance type of sport, and body size and mass are undoubtedly performance-related factors. Identifying factors such as physical size and structure, which may result in the best performance, can assist the exercise scientist and coach in selecting and developing talented athletes. There is, however, a lack of anthropometric data collected at either World Championship or Olympic Games level. The aims of this study were to describe and compare the morphology and basic strength characteristics of male and female heavyweight and lightweight rowers competing during 2022 World Championship (18. – 25. September, Račice, Czech Republic). A total of 68 athletes (of 46 male competitors: 15 competed in the lightweight category and 31 in the heavyweight category; of 22 female athletes: 6 competed in the lightweight category and 16 in the heavyweight category) were measured using anthropometric methods, bioimpedance analysis and performed a hand-grip test. Between heavyweight and lightweight male rowers there were a statistically and practically significant differences in all monitored aspects except the sport age, sitting height/body height ratio and arm span/body height ratio. Between heavyweight and lightweight female rowers there were also statistically and practically significant differences in all monitored aspects except the identical indicators as in male. Within our research it can be argued that female rowers are in many anthropometric aspects more similar to their male counterparts than to female rowers in the lightweight category. In some anthropometric aspects (BMI, thigh girth, calf girth), female rowers are even more similar to male heavyweight than to male lightweight rowers. The physical characteristics of elite male and female lightweight rowers differ radically from those of heavyweight. From a practical point of view, this research can be used to determine what type of somatotype should be recruited or selected for open category and what type for lightweight category in male and female rowing.